Holistic wellness in transitioning from sports experiences of former football collegiate athletes - Napiza, Denielle Joy F. 2001-
An athlete’s transition from sports is rarely straightforward, and the complex process of transitioning from sports may have significant effects on the student-athletes' holistic wellness. Studies have reported the differences in demographic variables, and the cultural factors of a successful transition from sports calls for a need in developing sport-specific interventions, and enhancing a sport's culture require an understanding of the unique wellness characteristics within sports. This study is focused on investigating the effects of transitioning from sports to the holistic wellness of former football collegiate student-athletes. Through the IS-WEL model of wellness, four participants were interviewed using a semi-structured interview and the findings were then interpreted using Thematic Analysis through a deductive method. The results showed wellness-related issues in their Creative Self, Coping Self, Essential Self, and Physical Self. Meanwhile, the Social Self was found to have played the most significant role in their transition from collegiate sports. This highlights the importance of social wellness in athletes’ transitions from sports, encouraging student-athletes to build relationships and explore identities beyond athletics. Furthermore, the study suggests increasing the number of participants, using other wellness models for further research, and exploring more factors.